"Dangerous" Historiographies: Minoru Hokari's observations and lived Aboriginal practices of history. Issue 1 (March 2013) - Guntarik, Olivia
Aboriginal historiographies challenge conventional interpreting of societies and cultures' histories which are often linear, singular, and excluding of other than dominant narratives. But alternative solutions to conventional history are often binarized as minority or oppositional groups and simply "accommodated" in what continues as the dominant story. The work of Japanese scholar Minoru Hokari from his time with Gurindji people, an Aboriginal Australian group from the Kalkaringi region in northern Australia, is discussed here as an innovative way of re-framing how we think outside such dichotomies. Following Hokari's lead the author's own cross-culture positioning is then used to explore Aboriginal construction of knowledge and history amongst the Ganai/Kurnai, the Aboriginal people originating from the region of Gippsland in southern Australia. This broadens the argument for valuing multiple alternative histories that such lived experience offers for majority and Indigenous peoples alike.